Climate Information and Forecasting for Development : Lessons from the 1997/98 El Nino - Van Aalst, Maarten K.; Fankhauser, Samuel; Kane, Sally M.; Sponberg, Kelly (World Bank, Washington, DC, 2014)
Human welfare and development are heavily influenced by climatic factors. As many as 95 percent of all disaster-related casualties occur in developing countries, and after an event the recovery often takes years. Natural disasters can significantly derail the process of social and economic development. The Bank has always supported reconstruction in countries affected by natural disasters. A forward-looking approach to disaster management is needed, in which natural hazards are screened, analyzed, and dealt with in an integrated fashion and in as routine and efficient a manner as are other risks affecting development. This paper argues that the effective use of climate information and forecasting should become an integral part of the new paradigm of comprehensive disaster management. Longer-range forecasts of many phenomena can now be produced at a time scale, reliability, and spatial resolution that make them useful for planning purposes. Forecasts of El Nino Southern Oscillation events are one such example, and their use for disaster management is the main focus of this paper. The use of climate information and forecasts requires strong local institutions, well-functioning procedures for information dissemination, and the trust and motivation of end-users.